2023
DOI: 10.3390/biomedicines11051381
|View full text |Cite
|
Sign up to set email alerts
|

Physical Training vs. Perindopril Treatment on Arterial Stiffening of Spontaneously Hypertensive Rats: A Proteomic Analysis and Possible Mechanisms

Abstract: (1) Background: Arterial stiffness is an important predictor of cardiovascular events. Perindopril and physical exercise are important in controlling hypertension and arterial stiffness, but the mechanisms are unclear. (2) Methods: Thirty-two spontaneously hypertensive rats (SHR) were evaluated for eight weeks: SHRC (sedentary); SHRP (sedentary treated with perindopril—3 mg/kg) and SHRT (trained). Pulse wave velocity (PWV) analysis was performed, and the aorta was collected for proteomic analysis. (3) Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The reduced aortic stiffness they observed seems to be connected to the elevated expression of the Ehd2 (EH domain-containing) protein, a component involved in the endothelial nitric oxide synthase (eNOS)-nitric oxide (NO) endothelial vasodilatory pathway. They succeeded in proving that the rigidityreducing effect of chronic exercise has a different mechanism [7]. The extremely complex nature of the renin-angiotensin system (RAS) is shown by another paper in this Special Issue.…”
Section: Pleiotropic Effects Of Ang IImentioning
confidence: 98%
See 1 more Smart Citation
“…The reduced aortic stiffness they observed seems to be connected to the elevated expression of the Ehd2 (EH domain-containing) protein, a component involved in the endothelial nitric oxide synthase (eNOS)-nitric oxide (NO) endothelial vasodilatory pathway. They succeeded in proving that the rigidityreducing effect of chronic exercise has a different mechanism [7]. The extremely complex nature of the renin-angiotensin system (RAS) is shown by another paper in this Special Issue.…”
Section: Pleiotropic Effects Of Ang IImentioning
confidence: 98%
“…Three papers which have been published in this Special Issue deal with such pleiotropic functions of the renin-angiotensin system (RAS). In an excellent study by Miotto et al [7] from the State University of Sao Paulo, Brazil, the aortic wall of perindopril-treated spontaneously hypertensive rats (SHR) was analyzed. Using the best available high throughput proteomic methods, they found that chronic treatment with the angiotensin converting enzyme (ACE) inhibitor perindopril in the artic wall altered 38 subcategories of cellular protein components, among them "supramolecular polymer", "heterotrimeric G protein complex", "actin cytoskeleton", "supramolecular fiber", "intermediate filament", "membrane raft" and "oxidoreductase" complexes.…”
Section: Pleiotropic Effects Of Ang IImentioning
confidence: 99%